Integrated Water Resource Management under Ecosystem Services Approach—The Chimulala Micro-watershed, Peru - Cifuentes-Herrera, L.F.; Romero-Duque, L.P.; Núñez, O.E.A.; Trilleras, J.M. (Springer, 2025)
This study evaluates the sociocultural valuation of ecosystem services (ES) within the Chimulala micro-watershed, Peru, to inform Integrated Water Resource Management (IWRM). Using surveys and focus groups, we gathered data from 35 stakeholders (11 institutional and 24 local actors) to assess perceptions, orientations, and anticipated changes regarding 15 identified ES. A land cover map was developed to support an expert-led ES assessment, categorizing capacity levels across different land types. Results showed unanimous agreement on the vital importance of the water supply service, with local actors identifying and valuing a broader array of ES than institutional counterparts. Multiple correspondence analysis highlighted differences in ES recognition between stakeholder groups, revealing that local actors ascribed greater importance to cultural and regulatory ES, while institutional actors prioritized provisioning services. Conflicts were identified regarding responsibilities for changes in ES provision, with local communities attributing threats primarily to mining, while institutional actors cited land use changes. This research underscores the value of sociocultural ES assessments in bridging divergent perspectives and enhancing the participatory foundation of IWRM, ultimately aiding in the design of inclusive, resilient water management policies.
Keywords: Stakeholders; Sociocultural valuation; Perception value; Orientation value; Change value and water management; https://purl.org/pe-repo/ocde/ford#5.04.06